O mesmo : tautologia e política na arte conceitual - Oliveira, Silfarlem Junior de (2014)
This research aims to discuss the concepts of tautology and politics from conceptual artistic production of the years 1960/70, especially the Anglo-Saxon analytic-linguistic aspect and the Latin American political-ideological conceptualism. Along this axi